Contributions to the discussion on the Fuegian productive matrix. Map of the Governance of Natural Resources in Tierra del Fuego (Desarrollo, Estado y Espacio, 2022)
The economic development of the Province of Tierra del Fuego is strongly conditioned by the industrial promotion policy carried out by the national government within the framework of Law 19640. From its approval in 1972 to the present day, the Regime has been subject to operational reconfiguration as a result of various measures taken by the national government. One of the most notorious changes is the modification of its priorities, from the extraction of natural resources to the development of the electronics industry. It should be noted that, although the Regime is implemented in the province, it is at the national level where the productive profile of Tierra del Fuego is defined. The purpose of this paper is to analyze these activities related to the extraction of natural resources, in particular, fishing, low-scale mining and forestry, through the design of governance maps. By means of this analytical tool, to make actors, articulations and rules of the game visible.
Keywords: Developing; Governance; Natural Resources; Public Politics